A Case Report of Multidisciplinary Diagnosis and Treatment of a Patient with Tuberous Sclerosis Complex and Multi-Organ Involvement - ZHENG Hua; ZHI Yunfei; YING Lujing; ZHU Lan; JI Mingliang; LIANG Ze; WANG Jiangshan; SHI Haifeng; ZHANG Weihong; XIAO Mengsu; ZHANG Yushi; XU Kaifeng; et al. (罕见病研究, 2024)
Tuberous sclerosis complex(TSC)is a rare genetic disease that can lead to benign dysplasia in multiple organs such as the skin, brain, eyes, oral cavity, heart, lungs, kidneys, liver, and bones. Its main symptoms include epilepsy, intellectual disabilities, skin depigmentation, and facial angiofibromas, whilst incidence is approximately 1 in 10 000 to 1 in 6000 newborns. This case presents a middle-aged woman who initially manifested with epilepsy and nodular depigmentation. Later, she developed a lower abdominal mass, elevated creatinine, and severe anemia. Based on clinical features and whole exome sequencing, the primary diagnosis was confirmed as TSC. Laboratory and imaging examinations revealed that the lower abdominal mass originated from the uterus. CT-guided biopsy pathology and surgical pathology suggested a combination of leiomyoma and abscess. With the involvement of multiple organs and various complications beyond the main diagnosis, the diagnostic and therapeutic process for this patient highlights the importance of rigorous clinical thinking and multidisciplinary collaboration in the diagnosis and treatment of rare and challenging diseases.